2020
DOI: 10.3389/fpsyg.2020.01416
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Expectation of New Project Income Under the Influence of the Entrepreneur’s Sentiment From the Perspective of Information Asymmetry

Abstract: The phenomenon of high first-day income and high break-up rate in China's capital market has long attracted the attention of investors. Based on the disagreement model, in combination with the information asymmetry theory and behavioral finance, a mathematical model was put forward to analyze the reasons and mechanisms for the excess return of the initial public offering (IPO) on the first-day under the influence of investors' sentiments. The analysis shows that the IPO first-day income is a function of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…According to Ajzen, Individuals’ behavioral beliefs have both positive and negative effects on their behavioral attitudes. Normative beliefs produce perceived social pressure or subjective norms, while control beliefs have a decisive effect on perceived behavioral control ( Ajzen, 2002 ; Zhong et al, 2020 ; As shown in Figure 1 ). García-Rodríguez considers that intention is an important factor in identifying someone’s motivations and characteristics in establishing entrepreneurial activities ( García-Rodríguez et al, 2017 ).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…According to Ajzen, Individuals’ behavioral beliefs have both positive and negative effects on their behavioral attitudes. Normative beliefs produce perceived social pressure or subjective norms, while control beliefs have a decisive effect on perceived behavioral control ( Ajzen, 2002 ; Zhong et al, 2020 ; As shown in Figure 1 ). García-Rodríguez considers that intention is an important factor in identifying someone’s motivations and characteristics in establishing entrepreneurial activities ( García-Rodríguez et al, 2017 ).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Entrepreneurship education is highly practical, so theory and practice should be combined. Highly experienced teachers with entrepreneurial backgrounds should be invited for a professional entrepreneurship course ( Zhong et al, 2020 ). Practice bases can be established by higher education institutions through cooperation with high-tech enterprises, such as science-entrepreneurship park and entrepreneurship education incubation base.…”
Section: Discussion On Cultivating Entrepreneurial Talentsmentioning
confidence: 99%
“…Then, a talent training plan that is recognized by the “government, school and enterprise” is formed. Third, the talent training goals finally formed in its plan should be diverse, taking into account the individual needs of students, so as to meet the local characteristics of each college and the differences of students ( Zhong et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%